Factors Affecting the Acceptance of the Use of Electronic Applications in the Light of the Unified Theory of Acceptance and Use of Technology UTAUT - Elsunaki, Mohamed; Elwalda , Abdulaziz (The Arab Journal of Administration, 2025)
Although the factors influencing the acceptance of the use of electronic applications have received great attention in previous literature, the level of their adoption in Libya is still low, and accordingly; The study aimed to identify the factors affecting the acceptance of the use of electronic applications in Libya, a field study on the Makani application, through the use of the Unified Theory of Acceptance and Use of Technology (UTAUT). The study population consisted of users of electronic applications in Libya. The study also used an online survey list using the Google Forms application to survey users’ opinions. There were (403) survey lists, and the number of valid and usable survey lists reached (366) survey lists. The data that was analyzed was Collected quantitatively using correlation and multiple linear regression, and control factors were analyzed using the Macro Process test. The study reached a set of results, the most important of which are: trust is the most important factor influencing acceptance of the use of electronic applications, followed by social influence, and then expected performance and expected effort, while the available facilities did not have an impact on acceptance of the use of electronic applications. The most prominent results of the control factors were: that sex had an effect between the dimensions of expected performance, confidence and acceptance of use, while age had an effect between the dimension of the expected effort and acceptance of use, and that experience It had an effect between the dimension of trust and acceptance of use.